2015
DOI: 10.1016/j.rpped.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Triagem neonatal de hemoglobinopatias no município de São Carlos, São Paulo, Brasil: análise de uma série de casos

Abstract: OBJECTIVE: To analyze the neonatal screening program for hemoglobinopathies in São Carlos, Southeast Brazil, by investigating a series of cases in which the screening test was abnormal. More specifically, it was aimed to know the information regarding the neonatal screening received by mothers at the hospital and at primary health care, in addition to information related to genetic counseling. METHODS: A descriptive study that enrolled 119 mothers, accounting for 73% of all children born between 2010 and 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
6
0
9
Order By: Relevance
“…An alarming result was the fact that only 3% of those mothers received adequate guidance on the Guthrie test. However, a recent survey showed that, in 93.3% of cases, the nurse was the health care professional responsible for the provision of information about neonatal screening to mothers, and the physicians were responsible for only 5.9% of the cases 21 . In another study in the city of Cáceres, Mato Grosso, Brazil, 51% of mothers reported having received information from nurses and 22.4% of them from physicians 17 …”
Section: Discussionmentioning
confidence: 99%
“…An alarming result was the fact that only 3% of those mothers received adequate guidance on the Guthrie test. However, a recent survey showed that, in 93.3% of cases, the nurse was the health care professional responsible for the provision of information about neonatal screening to mothers, and the physicians were responsible for only 5.9% of the cases 21 . In another study in the city of Cáceres, Mato Grosso, Brazil, 51% of mothers reported having received information from nurses and 22.4% of them from physicians 17 …”
Section: Discussionmentioning
confidence: 99%
“…A informação de prevalência das hemoglobinas S e C demostra relação entre as populações estabelecendo resultados semelhantes, não diferem comparado a pesquisas realizadas anteriormente em diversas regiões do País. Ressaltando a importância da realização e do PNTN com objetivo de reduzir a morbimortalidade por hemoglobinopatias, assim, possibilitando a implementação de programas mais efetivos de aconselhamento genético Lopes, et al, 2011;Cardoso, Macedo, Diedrich, Magalhães, & Castro, 2017;Silva, Baldim, Nhoncanse, Estevão, & Melo, 2015 de Teresina, que registrou alto Research, Society and Development, v. 9, n. 3, e01932259, 2020(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i3.2259 7 número de casos provavelmente decorrentes do município de Teresina ser o mais populoso do Estado. A Figura 1 apresenta a distribuição de ocorrência de hemoglobinas variantes por zona no município.…”
Section: Resultsunclassified
“…As hemoglobinopatias são doenças hereditárias mais frequentes a nível mundial, estimando-se que atinjam cerca de 7% da população no mundo (Marcão, Lopes, Sousa, Fonseca, & Rocha, 2016). Composta de um grupo heterogêneo de mais 100 doenças hereditárias, que em sua maioria é autossômicas recessivas, apresentando mais de 1.000 alelos mutantes, representadas principalmente pelas hemoglobinas S e C (HbS e HbC) em menor aparecimentos hemoglobinas D (HbD), hemoglobina fetal (HbF) e as talassemias, que se divide em alfa (α) e beta (β) é a segunda doença mais frequente e com maior importância clínica, a sua forma mais grave é chama de talassemia maior (portador homozigoto) e talassemia menor, ou traço talassêmico característico da herança de um único gene mutante (Silva, Baldim, Nhoncanse, Estevão, & Melo, 2015;Rosenfeld, et al, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For couples in whom both individuals have the SCT, identification of the condition and genetic counseling are important before starting a family 11 . Difficulty in distinguishing between the terms carrier and affected individuals was reported in two recent researches 12, 13. One showed that only 17 (14.3%) of the 119 mothers whose children presented an abnormal result in the screening test for hemoglobinopathies could acknowledge the difference between the trait and the disease 13 .…”
Section: Introductionmentioning
confidence: 99%